Multi‐institutional validation of a modified scheme for subcategorizing salivary gland neoplasm of uncertain malignant potential (SUMP). Issue 7 (30th May 2022) - Hang, Jen‐Fan; Lee, Jaslyn Jie Lin; Nga, Min En; Higuchi, Kayoko; Hirata, Yukiya; Wu, Howard H.; Allison, Derek B.; Gilbert, Jason D.; Lin, Oscar; Saieg, Mauro; de Arruda, Arthur Ferrari; Chen, Yun‐An; et al.
Abstract : BACKGROUND: The salivary gland neoplasm of uncertain malignant potential (SUMP) category in the Milan System is diagnostically challenging. This study aims to validate a modified scheme for subcategorizing SUMP in a large multi‐institutional cohort. METHODS: Retrospective review of salivary gland fine‐needle aspirations (FNAs) from 10 institutions were classified based on the Milan System. Cases diagnosed as SUMP with available cytology slides and surgical follow‐up were retrieved for review and subcategorized based on a modified scheme as follows: basaloid SUMP (B1: absent/scant nonfibrillary matrix; B2: presence of nonfibrillary/mixed‐type matrix), oncocytic/oncocytoid SUMP (O1: with mucinous background; O2: without mucinous background), and SUMP not otherwise specified (NOS). RESULTS: A total of 742 (7.5%) cases from 9938 consecutive salivary gland FNAs were classified as SUMP. Among them, 525 (70.8%) had surgical follow‐up and 329 (62.7%) were available for review. The overall risk of malignancy (ROM) of SUMP was 40.4%. There were 156 cases (47.4%) subcategorized as basaloid SUMP with a ROM of 36.5%, 101 (30.7%) as oncocytic/oncocytoid SUMP with a ROM of 52.5%, and 72 (21.9%) as SUMP NOS with a ROM of 31.9%. The ROM of oncocytic/oncocytoid SUMP was significantly higher than basaloid SUMP ( P = .0142) and SUMP NOS ( P = .0084). No significant differences in ROM were noted between B1 and B2 (36.7% vs 36.4%, P = 1.0000) and O1 and O2 (65.2% vs 48.7%, P = .2349). CONCLUSIONS: The ROM of oncocytic/oncocytoid SUMP was 52.5% and significantly higher than that of basaloid SUMP (36.5%, P = .0142) and SUMP NOS (31.9%, P = .0084), whereas no significant differences in ROM were noted for cases with different types of extracellular matrix or background material.; Abstract : Salivary gland neoplasms of uncertain malignant potential (SUMP) comprised 7.5% of all salivary gland fine‐needle aspirations in our large multi‐institutional study, with an overall risk of malignancy (ROM) of 40.4% and risk of neoplasm of 96.0%. The ROM of oncocytic/oncocytoid SUMP was 52.5% and significantly higher than that of basaloid SUMP (36.5%, P = .0142) and SUMP not otherwise specified (31.9%, P = .0084), whereas no significant difference in ROM was noted for cases with different types of extracellular matrix or background material.